Diaphragmatic weakness in hereditary motor and sensory neuropathy. Issue 4 (April 1990) - Hardie, R; Harding, A E; Hirsch, N; Gelder, C; Macrae, A D; Thomas, P K
Abstract : Six patients severely affected by hereditary motor and sensory neuropathy (HMSN), four type I and two type II, had clinical evidence of diaphragmatic weakness. One presented with cardiorespiratory failure secondary to nocturnal hypoventilation, and three others were unable to lie flat because of dyspnoea. Diaphragmatic paralysis should be considered as a cause of respiratory or cardiac failure in cases of HMSN.